Transmission of Government Spending Shocks in the Euro Area: Time Variation and Driving Forces - Markus Kirchner; Jacopo Cimadomo; Sebastian Hauptmeier (Tinbergen Institute, 2010)
This paper provides new evidence on the effects of government spending shocks and the fiscal transmission mechanism in the euro area for the period 1980-2008. Our contribution is two-fold. First, we investigate changes in the macroeconomic impact of government spending shocks using time-varying structural VAR techniques. The results show that the short-run effectiveness of government spending in stabilizing real GDP and private consumption has increased until the end-1980s but it has decreased thereafter. Moreover, government spending multipliers at longer horizons have declined substantially over the sample period. We also observe a weaker response of real wages and a stronger response of the nominal interest rate to spending shocks. Second, we provide econometric evidence on the driving forces behind the observed time variation of spending multipliers. We find that a higher ratio of credit to households over GDP, a smaller share of government investment and a larger share of public wages over total government spending have led to decreasing contemporaneous multipliers. At the same time, our results indicate that higher government debt-to-GDP ratios have negatively affected long-term multipliers.
Keywords: C32; E62; H30; H50; 330; Government spending shocks; Fiscal transmission mechanism; Structural change; Bayesian analysis; Structural vector autoregressions; Time-varying parameter models; Öffentliche Ausgaben; Schock; Geldpolitische Transmission; Strukturwandel; Bayes-Statistik; VAR-Modell; Schätzung; EU-Staaten